2021 Comprehensive Surveillance Review : Modalities for Modernizing Surveillance. (Policy Papers; Policy Paper ;, 2021)
Modern Fund surveillance needs to be more targeted, topical and timely, better interconnected and better informed. Modernizing surveillance will likely require additional resources, although estimates are highly uncertain at this stage. The paper offers a tentative costing of new proposals with significant budgetary implications. Other proposals could rely on optimizing processes, while others are underway and funded separately; the resource implications of yet others are being picked up in context of other workstreams. Estimates do not include short-term transition costs or pressures on support services and are subject to a significant degree of uncertainty. A flexible approach to implementing the new modalities, characterized by experimentation and learning-by- doing-a 'sandbox' for new modalities-is proposed.